The factors that affect the purchase decision of furniture in Islamic concept / Asyila Sasha Mohd Hanif and Muhammad Nazmi Mat Nor - Mohd Hanif, Asyila Sasha; Mat Nor, Muhammad Nazmi (Faculty of Business and Management, 2014)
This research was conducted to carry out a study entitled “The Study of Factors That Affect the Purchase Decision of Furniture in Islamic Concept”. The purpose of this study is to investigate the element in each factor that affect the purchase decision of furniture in Islamic concept. Besides that, this purpose is to investigate which factors contribute the most towards the furniture purchase decision in Islamic concept. Basically, it consists of three factors that affect the furniture purchase decision in Islamic concept which are Islamic advertising, wealth and income and Islamic pricing. For this study, 60 Muslim respondents who are already working and have a house of their own were chosen randomly among Malaysian because that indicates that most probably they have the experience in purchasing furniture. All the data collected through the questionnaires were analyzed systematically by Statistical Package for Social Science (SPSS). The conclusion of this study is the outcome from the data analysis and findings. A clear findings and results were observed based on frequency and descriptive statistic. The result showed that the most factors that contributes to the purchase decision of furniture in Islamic perspectives was Islamic pricing. The recommendation is also provided in this research to emphasize the important of purchase decision of furniture in Islamic concept.